Presentation: Internationalization of Higher Education in the Ibero-American Territory - Pereira, Elisabete Monteiro de Aguiar; Almeida, Maria de Lourdes Pinto de (Universidade Estadual de Campinas, 2019)
The articles of this Dossier are, in general, related to the results of a large research project jointly developed among 22 universities from 9 countries, on the topic of internationalization in higher education. The project is coordinated by a research group of international scope called GIEPES - International Group of Studies and Research on Higher Education, based in the Faculty of Education of the State University of Campinas - Unicamp. This project includes researchers and scholars of higher education issues, who also belong to the Ibero-American Network.